Hepatic gamma-glutamyltransferase activity in alcoholic fatty liver: comparison with other liver enzymes in man and rats. Issue 7 (July 1983) - Teschke, R; Neuefeind, M; Nishimura, M; Strohmeyer, G
Abstract : Compared with controls, patients with alcoholic fatty liver showed a significant increase of gamma-glutamyltransferase activity both in the liver and serum, whereas alkaline phosphatase activity was raised only in the liver but not in the serum. The activities of other enzymes such as aspartate aminotransferase, alanine aminotransferase and glutamate dehydrogenase remained virtually unchanged in the liver of patients with alcoholic fatty liver but were strikingly enhanced in the serum. The hepatic and serum alterations of enzymic activities observed in patients with alcoholic fatty liver could be reproduced in the rat model of alcoholic fatty liver only for gamma-glutamyltransferase but not for the other enzymes tested, substantiating evidence that the animal model may serve as an appropriate tool for studying interactions between alcohol and gamma-glutamyltransferase. The present experiments also indicate that the primary cause for increased serum gamma-glutamyltransferase activities associated with prolonged alcohol consumption is hepatic enzyme induction rather than liver cell injury.